A Rationale for a Translator-Centered, Process-Oriented Methodology for Translation Quality Assessment (2005)
ABSTRACT: Normally the translation scholars concerned with the lack of objective parameters with which to carry out effective translation quality assessment processes have conducted their studies based on what is most easily observable: translated texts. In this article, we propose a methodology for the assessment of translated texts within an undergraduate translation program that takes into account not only the final product of the translation, but also the processes that led to the translated text and the subject who produced it.